2021
DOI: 10.12944/carj.9.3.05
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Germination of Seeds of Cassia abbreviata and Senegalia nigrescens Using Pre-Sowing Seed Treatments in Botswana

Abstract: Cassia abbreviata and Senegalia nigrescens are indigenous trees found in North and Central regions of Botswana. However, inadequate knowledge of their silviculture and decline in population due to deforestation, expanding settlements, infrastructure and agriculture are major threats to most indigenous tree species in Botswana. Like many indigenous tree species, Cassia abbreviata and Senegalia nigrescens are slow-growing and are threatened by overexploitation for numerous uses. Because of the increased demand f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…This could be explained by the high heat that the boiling water transmitted through the seed coat to the interior parts, which most likely killed the embryo (Kahaka et al 2018;Rampart et al 2021b). The study's findings are in line with earlier investigations on other native tree species in Botswana (Kahaka et al 2018;Mojeremane et al 2018;Odirile et al 2019;Botumile et al 2020;Rampart et al 2021aRampart et al , 2021b, which revealed that the seeds soaked in boiling water had the lowest rate of germination.…”
Section: Seed Germinationsupporting
confidence: 91%
“…This could be explained by the high heat that the boiling water transmitted through the seed coat to the interior parts, which most likely killed the embryo (Kahaka et al 2018;Rampart et al 2021b). The study's findings are in line with earlier investigations on other native tree species in Botswana (Kahaka et al 2018;Mojeremane et al 2018;Odirile et al 2019;Botumile et al 2020;Rampart et al 2021aRampart et al , 2021b, which revealed that the seeds soaked in boiling water had the lowest rate of germination.…”
Section: Seed Germinationsupporting
confidence: 91%